Meow-Meow food dispenser using Internet Of Things (IOT) programme / Nor Diyana Md Sin ... [et al.] - Md Sin, Nor Diyana; Saiful Azam, Saifaris Azizi; Osman, Muhamad Danial; Hussin, Mohamad Zhafran; Sidik, Norbaiti; Hasan, Khairul Kamarudin (2021)
This project is about a pet feeding machine where the feeder automatically feeds the pet according to the command made by the owner via a mobile phone. This project set up is controlled by a mobile app where the command is to feed the cat or not. The cats at home can get food and owners can supervise the pet feeding time using the mobile app to always ensure the cat is fed especially when the owner is busy. The food for the cat is stored inside a box or storage. The food would be served to the cats based on the amount specified by the owner to feed the pets. It is a smart idea to prevent cats from hunger if no one is at home. The cost of taking care of a cat is reduced due to the launch of such device in the market. Such idea is getting popular globally due to the automatic system and mobile app involvement. The other factor is due to the ease to operate the device to feed the cat. Besides that, the device was also installed with a camera in order to monitor the cat's condition. By adding a camera to the device, the owners will know their cats' health conditions so if there is something wrong with their cats, the owners can respond fast.